How Does Psycap Encourage Increased Lecturer Affective Commitment? Revealing The Role of Authentic Leadership - Paulus Eddy Suhartanto; Markus Hartono; Frikson Christian (Journal of Educational, Health and Community Psychology, 2023)
AbstractCurrently, organizational affective commitment was still one of the important issues in higher education. Previous research had shown that affective commitment could be explained in a variety of ways according to the context of the theoretical approach, cultural context and type of organization.  With a personal  and value perpsective, authentic psychology and leadership could be placed as important issues in influencing affective commitment.  In today's complex and fast-moving organizations, affective commitment behavior is critical to organizational success. Psycap and authentic leadership proved to be strong predictors of affective commitment, but the underlying mechanisms remain unclear. This study aims to examine the effect of psycap on the affective commitment of lecturers, where authentic leadership as the mediator. This research is a quantitative research involving 401 lecturers in Indonesia as research subjects. The results of this study show that authentic leadership partially mediates the influence of psycap on the affective commitment of APTIK lecturers. Increasing psycap will increase affective commitment both directly and through increasing the authentic leadership of lecturers. The results of this research can be used by government officials and universities as review material.Key words: affective commitment, authentic leadership, psycap, lecturer, college